Calligraphy Text Types Recognition Using Learning Vector Quantization - Mhd Furqan; Abdul Halim Hasugian; Ziqra Addilah (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
Calligraphy is the art of beautiful writing. The term calligraphy comes from simplified English (calligraphy) taken from the Latin word "kalios" which means beautiful, and "graph" which means writing or script. The art of writing Arabic letters is called the science of khat, known as the science of Arabic calligraphy or Islamic calligraphy. There are many types and varieties of Islamic calligraphy. Each has a different form and function. There are seven types of calligraphy that are popular and known by lovers of calligraphy art in Indonesia, such as, Khat Naskhi, Tsuluts, Farisi, Riq'ah, Diwani, Diwani Jali, and Kufi. The method commonly used to identify what type of calligraphy is made is by looking directly at the shape and characteristics of the calligraphy itself (calligraphy experts). Here the author tries to create a computerized calligraphy type recognition system using the Learning Vector Quantization method. Where this method is a method that works with each unit of output representing a class. So with this system, we can recognize the type of calligraphy text computerized. The accuracy value obtained in the results of calligraphy image recognition is 75%.